Lovely war - Berry, Julie, 1974- (Viking, an imprint of Penguin Random House LLC, New York, 2019)
"In the perilous days of World Wars I and II, the gods hold the fates -- and the hearts -- of four mortals in their hands. They are Hazel, James, Aubrey, and Colette. A classical pianist from London, a British would-be architect-turned-soldier, a Harlem-born ragtime genius in the U.S. Army, and a Belgian orphan with a gorgeous voice and a devastating past. Their story, as told by goddess Aphrodite to her husband, Hephaestus, and her lover, Ares, is filled with hope and heartbreak, prejudice and passion, and reveals that, though War is a formidable force, it's no match for the transcendent power of Love"--Adapted from jacket